Utilizing the 3Ms of process improvement : a step-by-step guide to better outcomes leading to performance excellence. - Morrow, Richard, 1956- (CRC Press, 2012)
Why is it that some improvement efforts succeed while others fail despite robust change management programs and the often do-or-die pressure to improve? Quite simply, there are three elements that separate those that succeed from those that fail. They are the 3Ms-Measure, Manage to Measure, and Make-it-Easy.Complete with forms, templates, and case studies from the aviation and manufacturing industries, Utilizing the 3Ms of Process Improvement supplies step-by-step guidance on how to use the 3Ms to achieve performance excellence that lasts. Suitable for a wide.